Analysis of the seismic behavior of traditional Chinese timber structures in the Tang Dynasty. (July 2022) - Wang, Juan; Cui, Zhihan; Yu, Lei; Xu, Renwen; Yang, Qingshan
Abstract: The palace-style timber structure for the Tang Dynasty in China is a world cultural heritage of great value. The East Palace of Foguang temple in Shanxi Province, which is more than 1000 years old, has experienced many earthquakes without collapsing, indicating an excellent anti-seismic performance. The structure has three apparent horizontal layers: the column frame layer with a column foot joint floating directly on the base stone, the bracket complex and beam layer with a relatively high rigidity, and the roof truss layer. This paper performs a dynamic time-history analysis for a typical timber frame in the Tang Dynasty in order to study the seismic performance of the structure and the energy consumption characteristics of the structural layers. A refined solid finite element model is established with the substructure verified by experiments. Dynamic parameters, such as frequency, vibration mode, acceleration response, and displacement response, are studied. The influences of the seismic waves, the vertical load, and the structural configuration are also discussed. The results show that the column foot and head joints give the structure a good deformation capacity. The column layer rotates under seismic action, while the bracket complex layer has a good integrity and moves horizontally with the column head. Column rocking reduces the transmission of vibration energy to the upper layer structure. The multilayer superposition of the bracket complex and the beam layer attenuates the seismic effects. The results reveal that the timber frame column and upper laminated layers have a good earthquake resistance.